IMPLEMENTATION OF A NOVEL INTERVENTION TO CARE FOR ELDERLY PATIENTS WHO FALL: PARAMEDICS' VIEWS. Issue 5 (18th April 2015) - Chatters, Robin; Porter, Alison
Abstract : Background: The SAFER 2 study, in three UK ambulance services, evaluated a complex intervention to support paramedics safely to leave older patients at home with referral to a falls service, following a call to 999 for a fall. The intervention comprised a training programme, referral pathway, clinical support, clinical decision flowchart and referral feedback. Normalisation Process Theory (NPT) examines the factors required for successful implementation of an intervention such as SAFER 2 into routine practice, through four components: coherence, cognitive participation, collective action and reflexive monitoring. We used NPT to frame an analysis of paramedics' views of implementation of SAFER 2. Methods: Focus groups and individual interviews were carried out with paramedics before and after the trial, and were recorded and transcribed in full. Transcripts were analysed using the framework approach, informed by NPT, by a team of four researchers. Results: Pre-trial, there were was not a clear or consistent understanding across sites of what the intervention was, and how it was distinct from similar interventions (coherence). Paramedics anticipated benefits of the new intervention, including improved patient care and job satisfaction, and thought that the referral pathway would be used widely (cognitive participation). During the trial, paramedics found that implementing the intervention led to increases of time on scene (Collective action). The intervention was perceived as advantageous to the ambulance service and patients in post-trial focus groups; paramedics from all three sites suggested improvements to the process which included simplification of the intervention (reflexive monitoring). Conclusion: Usage of NPT to support analysis of paramedic views on implementation of the SAFER 2 intervention highlighted issues with coherence and collective action that may have affected the trial. The novel intervention was seen as beneficial by paramedics during both pre- and post-trial interviews, although barriers to utilisation were identified.